Two-dimensional conjugated metal-organic frameworks (2D c -MOFs): chemistry and function for MOFtronics - Wang, Mingchao; Dong, Renhao; Feng, Xinliang (Chemical Society reviews, 2021)
The 21st century has seen a reinvention of how modern electronics impact our daily lives; silicon-electronics and organic electronics are currently at the core of modern electronics. Recent advances have demonstrated that conductive metal-organic frameworks (MOFs), as another unique class of electronic materials, are emerging to provide additional possibility for multifunctional electronic devices that brings us "MOFtronics". Typically, two-dimensional conjugated MOFs (2D c-MOFs) are a novel class of layer-stacked MOFs with in-plane extended π-conjugation that exhibit unique properties such as intrinsic porosity, crystallinity, stability, and electrical conductivity as well as tailorable band gaps. Benefiting from their unique features and high conductivity, 2D c-MOFs have displayed great potential for multiple high-performance (opto)electronic, magnetic, and energy devices. In this review article, we introduce the chemical and synthetic methodologies of 2D c-MOFs, intrinsic influences on their electronic structures and charge transport properties, as well as multifunctional applications of this class of materials for MOFtronics and potential power sources for MOFtronics. We highlight the benefits and limitations of thus-far developed 2D c-MOFs from synthesis to function and offer our perspectives in regard to the challenges to be addressed.